Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s10072-014-1982-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute optic neuritis: retinal ganglion cell loss precedes retinal nerve fiber thinning

Abstract: Optic neuritis (ON) causes axonal loss as reflected by thinning of retinal nerve fiber layer (RNFL) and can be tracked by optical coherence tomography (OCT) about 6 months after ON onset, when swelling of optic nerve head (ONH) has vanished. Changes of macular ganglion cell layer (GCL) thickness provide another window to track the disease process in ON. GCL thinning over time in relation to RNFL change after ON remains elusive. Using OCT, we followed 4 patients with acute unilateral isolated ON for more than 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 6 publications
6
40
1
Order By: Relevance
“…These results show that the GCIPL thickness is less affected by optic disc edema, thereby supporting the results of a previous study regarding GCL thickness as a factor for monitoring the retinal ganglion cell status after acute ON. 14 Previous studies have reported a significant correlation among RNFL thickness, VA, and VF. 10,14 Trip et al 10 reported that there were significant relationships among RNFL thickness and VA, VF, color vision, and the visualevoked potential (VEP) amplitude.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…These results show that the GCIPL thickness is less affected by optic disc edema, thereby supporting the results of a previous study regarding GCL thickness as a factor for monitoring the retinal ganglion cell status after acute ON. 14 Previous studies have reported a significant correlation among RNFL thickness, VA, and VF. 10,14 Trip et al 10 reported that there were significant relationships among RNFL thickness and VA, VF, color vision, and the visualevoked potential (VEP) amplitude.…”
Section: Discussionmentioning
confidence: 94%
“…14 Previous studies have reported a significant correlation among RNFL thickness, VA, and VF. 10,14 Trip et al 10 reported that there were significant relationships among RNFL thickness and VA, VF, color vision, and the visualevoked potential (VEP) amplitude. Walter et al 4 demonstrated that GCIPL thinning is most significantly correlated with visual function in MS patients with and without a history of acute ON and may serve as a useful structural marker of the disease.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We congratulate Huang-Link et al [1] for their report entitled 'Acute optic neuritis: retinal ganglion cell loss precedes retinal nerve fiber thinning'. The authors reported the longitudinal OCT results of four patients with optic neuritis and showed that ganglion cell layer (GCL) thickness decreased before the thinning in retinal nerve fiber layer (RNFL).…”
Section: Dear Editormentioning
confidence: 96%